SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SEPEDA MOTOR DENGAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS WEB - Aryanto, Rudi; Fajrin, Alfannisa Annurrullah (LPPM Universitas Putera Batam, 2020)
At Indonesia, there are many kinds of motorcycle producer and each of them have very own strengths and uniqueness in term of design, type, to the cylinder capacity. But variety of the motorcycle product makes the consumer having trouble to choose the suitable one for them. For this matter, there are needed a decision-making system that can help the user choose the suitable motorcycle and even provide for the alternative. For this decision-making system, Simple Additive Weighting method was chosen because this method places a weight on each criteria and filter them out until reach best choice and capable to provide the alternatives. The design of web-based motorcycle decision making system uses the simple additive weighting method and was developed using PHP as programming language and MySQL as database system.